Theoretical study of photoelectron angular distributions in single-photon ionization of aligned N2 and CO2 - Jin, Cheng; Le, Anh-Thu; Zhao, Song-Feng; Lucchese, R. R.; Lin, C. D. (My University, 2010)
We calculate photoelectron angular distributions (PADs) resulting from single-photon (43 eV) ionization of molecules that have been transiently aligned with a short laser pulse. The total ionization cross sections of N2 and CO2 vs the time delay between the aligning laser pulse and the soft x-ray photon are calculated and compared to experimental results reported by I. Thomann et al. [J. Phys. Chem. A 112, 9382 (2008)]. We present the PADs from these aligned molecules in the laboratory frame which can be compared directly with future experiments from aligned N2 and CO2. The alignment dependence of single-photon ionization, multiphoton ionization, and high-order harmonic generation are also analyzed.